PENGELOLAAN USAHA PONDOK WISATA (HOMESTAY) SEBAGAI RUMAH SINGGAH RAMAH LINGKUNGAN - Koestanto, Djoko (Gemawisata: Jurnal Ilmiah Pariwisata, 2014)
The term Pondok Wisata known in western countries as Homestay, which optionally can be interpreted as Resident Family or Stay Together Family, as usual House Live in general (Ordinary household).Management Pondok Wisata done by the owner cottage itself as individual businesses, and all efforts are made to meet the economic needs of the family then the dasarnnya not memerllukan business license of its own, but people penngelola cottage must report to the local government / office of Tourism will be the presence of management cottage The tour ..In the operation of Pondok Wisata further, there is a build / create new buildings outside the building House Live there previously, some are utilizing long and inhabited dwelling house together well all family members and tourists in an environment where the family lived with memenfaatkan ruangan- room / rooms that exist both in the roof or separately, in principle, to host as head of the family had to stay living together diantarannya, it is to be able to blend interact with tourists who are staying as a unity of family members where managers act or considered as head of the family or host (Host). Another effort other accommodation (hotels) where the owner is not required to tinnggal place of business. So to say that the cottage is a business that has to "typical" an tidk separate businesses owned by other accommodation, and it is the main attraction for tourists. still have its services to a unit owner.